Detection of Salmonid IgM Specific to the Piscine Orthoreovirus Outer Capsid Spike Protein Sigma 1 Using Lipid-Modified Antigens in a Bead-Based Antibody Detection Assay - Teige, Lena Hammerlund; Kumar, Subramani; Johansen, Grethe M.; Wessel, Øystein; Vendramin, Niccolò; Lund, Morten; Rimstad, Espen; Boysen, Preben; Dahle, Maria K. (Frontiers in Immunology, 2019)
Bead-based multiplex immunoassays are promising tools for determination of the specific humoral immune response. In this study, we developed a multiplexed bead-based immunoassay for the detection of Atlantic salmon (Salmo salar) antibodies against Piscine orthoreovirus (PRV). Three different genotypes of PRV (PRV-1, PRV-2 and PRV-3) cause disease in farmed salmonids. The PRV outer capsid spike protein σ1 is predicted to be a host receptor binding protein and a target for neutralizing and protective antibodies. While recombinant σ1 performed poorly as an antigen to detect specific antibodies, N-terminal lipid modification of recombinant PRV-1 σ1 enabled sensitive detection of specific IgM in the bead-based assay. The specificity of anti-PRV-1 σ1 antibodies was confirmed by western blotting and pre-adsorption of plasma. Binding of non-specific IgM to beads coated with control antigens also increased after PRV infection, indicating a release of polyreactive antibodies. This non-specific binding was reduced by heat treatment of plasma. The same immunoassay also detected anti-PRV-3 σ1 antibodies from infected rainbow trout. In summary, a refined bead based immunoassay created by N-terminal lipid-modification of the PRV-1 σ1 antigen allowed sensitive detection of anti-PRV-1 and anti-PRV-3 antibodies from salmonids.